2022
DOI: 10.15420/aer.2021.37
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Cavotricuspid Isthmus Ablation in Atrial Fibrillation without Documented Typical Atrial Flutter: A Systematic Review and Meta-analysis

Abstract: Background: The advantage of prophylactic cavotricuspid isthmus (CTI) ablation for AF patients without documented atrial flutter is still unclear. The present study aimed to evaluate the role of prophylactic CTI ablation in this population. Methods: A systematic review and meta-analysis study was conducted. The overall effects estimation was conducted using random effects models. The pooled effects were presented as the risk difference and standardised mean difference for dichotomous and continuous outcomes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…17,18,25–27,48,49 Conversely, prophylactic catheter ablation of the CTI in patients without documented or inducible AFL likely has minimal benefit. 50 Alternatively, in 1 study, cryoballoon PVI as first-line treatment for AFL is equally effective compared with standard CTI ablation for preventing recurrence of atrial arrhythmia and better at preventing new-onset AF. 51 Several randomized trials have compared catheter ablation to AADs as first-line therapy for AF.…”
Section: Rhythm Controlmentioning
confidence: 99%
“…17,18,25–27,48,49 Conversely, prophylactic catheter ablation of the CTI in patients without documented or inducible AFL likely has minimal benefit. 50 Alternatively, in 1 study, cryoballoon PVI as first-line treatment for AFL is equally effective compared with standard CTI ablation for preventing recurrence of atrial arrhythmia and better at preventing new-onset AF. 51 Several randomized trials have compared catheter ablation to AADs as first-line therapy for AF.…”
Section: Rhythm Controlmentioning
confidence: 99%
“…More unexpected is the finding that larger right/left atrial volumes were not associated with the development of AFL on multivariate analysis; I suspect that the limited number of patients included in the study prevents a more detailed analysis that could yield a picture more adherent to the clinical reality. Assigning a precise cut‐off value of RACT for the future development of typical AFL is a “debatable” action, just in terms of “let's do cavotricuspid ablation” as an empirical and prophylactic maneuver 9 . In this regard, I'd be cautious, awaiting more robust and consistent data from larger population studies.…”
Section: So Is That Simple?mentioning
confidence: 99%
“…Assigning a precise cut-off value of RACT for the future development of typical AFL is a "debatable" action, just in terms of "let's do cavotricuspid ablation" as an empirical and prophylactic maneuver. 9 In this regard, I'd be cautious, awaiting more robust and consistent data from larger population studies. On the contrary, I give credit to the authors that longer RACT can be found in patients undergoing AF ablation and without clinical history of typical AFL.…”
Section: So Is That Simple?mentioning
confidence: 99%
“…Whereas ablation of the flutter circuit is indicated in patients with documented AFL, it is often considered in those without a documented AFL history, but high risk of unrecognized AFL or development of AFL in the future 5 . The practice of empiric flutter ablation is employed to prevent symptomatic recurrence and attenuate stroke risk in a group that may eventually present with thromboembolic complications as the first indication of AFL 6,7 . A simple diagnostic maneuver to determine the existence of a potential AFL circuit, and therefore a risk of occult or future AFL, would be very useful.…”
Section: Introductionmentioning
confidence: 99%
“…5 The practice of empiric flutter ablation is employed to prevent symptomatic recurrence and attenuate stroke risk in a group that may eventually present with thromboembolic complications as the first indication of AFL. 6,7 A simple diagnostic maneuver to determine the existence of a potential AFL circuit, and therefore a risk of occult or future AFL, would be very useful. This could support the decision on whether to empirically ablate a flutter circuit at time of ablation for other rhythms, such as atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%